Research on target recognition technology of GISC spectral imaging based on active laser lighting - Li, Meixuan; Li, Yanqiu; Wang, Hong (Frontiers in Physics, 2022)
Aiming at the application requirements of spectral imaging technology in satellite remote sensing, biomedical diagnosis, marine detection and rescue, agricultural and forestry monitoring and classification, military camouflage identification, etc., this paper uses 532nm and 650nm lasers as light sources, and uses multi-spectral intensity correlation imaging equipment—snapshot spectroscopic cameras based on ghost imaging via sparsity constraints (GISC) enable precise identification of targets. In this paper, the principle of snapshot GISC spectral imaging is expounded, and the experimental research work of GISC spectral imaging target recognition technology based on active laser illumination is carried out. The experimental results show that using a 532 nm laser as the light source to illuminate the target object can accurately identify the green target letter "I"; using a 650nm laser as the light source to illuminate the target object can accurately identify the red target letter "Q". And gives spectral imaging results of the color target "QIT" acquired by the GISC spectroscopic camera through a single exposure at the wavelength range from 446nm to 698nm, with both pseudo-color map and color fusion map. In order to further illustrate the feasibility of the experiment, the spectral distribution of the reconstructed image is analyzed, which has important practical significance and engineering value.